On Social and Cultural Exclusion in the Southern Part of Klaipėda: An Essay in Symmetrical Anthropology - Gajauskas, Auridas (Sociologija. Mintis ir veiksmas, 2025)
This essay explores the social and cultural marginalization of the southern neighborhoods of Klaipėda, Lithuania. The approach is based on an expanded methodology of symmetrical anthropology that includes nonhuman actors and organizations in addition to human social and cultural interactions. The marginalization of this locality is first demonstrated by examining the socio-spatial relations that contribute to its social isolation from the city’s more prestigious districts, as well as by addressing the neglect of natural diversity and the anthropocentric degradation of local landscapes. The essay then analyzes how social and cultural tensions between Lithuanian and Russian-speaking residents manifest within the context of urban renewal initiatives. Finally, it assesses practices aimed at “filling” critical spaces—such as the display of artworks in public places, the construction of children’s playgrounds, and the donation of spatial art objects to the city—demonstrating how these interventions reflect the relationship between society, its institutions, and the role of art and artists.